2020
DOI: 10.1101/2020.04.16.045245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell lineages reveal the rates, routes, and drivers of metastasis in cancer xenografts

Abstract: N.Y.).One Sentence Summary: Detailed single-cell phylogenies capture the frequency, tissue routes, and seeding patterns of metastasis in vivo. Abstract:25 2 Consequential events in cancer progression are typically rare and occur in the unobserved past. Detailed cell phylogenies can capture the history and chronology of such transient events -including metastasis. Here, we applied our Cas9-based lineage tracer to study metastatic progression in a lung cancer xenograft mouse model, revealing the underlying rates… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 106 publications
4
90
0
Order By: Relevance
“…Such methods can be readily coupled to single-cell RNA sequencing (scRNA-seq) to explicitly relate cell lineage histories with transcriptional states [6][7][8] . Until recently 9,10 , GESTALT and related methods have primarily been applied to early development, e.g. by injection of CRISPR/Cas9 reagents into zygotes and subsequent profiling of edited barcodes and single cell transcriptomes from the resulting multicellular organism.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods can be readily coupled to single-cell RNA sequencing (scRNA-seq) to explicitly relate cell lineage histories with transcriptional states [6][7][8] . Until recently 9,10 , GESTALT and related methods have primarily been applied to early development, e.g. by injection of CRISPR/Cas9 reagents into zygotes and subsequent profiling of edited barcodes and single cell transcriptomes from the resulting multicellular organism.…”
Section: Introductionmentioning
confidence: 99%
“…Karthaus and colleagues recently found that luminal prostate cells that persist after ADT in a mouse model can contribute to tissue regeneration of the normal prostate epithelium by assuming stem-like transcriptional properties (Karthaus et al, 2020). Similar phenotypic features important for routing and rates of metastasis formation in lung cancer models have been found to be driven by differences in gene expression (Quinn et al, 2021). Similarly, here we find that during exposure to AR targeting agents, a small proportion of persistent cells remain transcriptionally unperturbed by the treatment, consistent with our recent findings of subclones with high metastatic potential interlayered within the primary untreated lesions (Woodcock et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Using PC specimen tumor DNA, we recently showed the presence of subclones within the primary tumors that preserve the ability to expand and metastasize years after treatment and are found interlayered within different lesions of multifocal tumors (Woodcock et al, 2020). Similarly, a recent work studying lung cancer metastases found that metastatic capacity arises from pre-existing and heritable differences in gene expression (Quinn et al, 2021). Therefore, we hypothesized that the persistent cluster 11, Stem-Like, initial cluster 10, and PROSGenesis signatures could be able to capture signals from such types of pre-existing subclones with metastatic potential in primary untreated tumors.…”
Section: Resultsmentioning
confidence: 98%
“…The authors concluded that axillary LN metastases contribute minimally to distant seeding in breast cancer patients [ 146 , 147 ]. Further, using a Cas9-based method that allows the long-term single-cell lineage tracing of cancer cells in an orthotopic lung cancer model in mice, some distant metastasis was traced back to an origin in mediastinal lymph nodes [ 148 ]. Collectively, these data show that in some—but not all—cancer models and patients, LNMs can serve as a source of distant metastasis.…”
Section: Lymph Node Metastasismentioning
confidence: 99%